Influencing factors and predictive indicators of return of spontaneous circulation in in-hospital cardiac arrest - Wang, Xiao; Kong, Tao (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIn-hospital cardiac arrest (IHCA) refers to the occurrence of cardiac arrest in hospitalized patients requiring chest compressions and/or defibrillation, with only about one-third of patients achieving return of spontaneous circulation (ROSC) after cardiopulmonary resuscitation. Pan-immune-inflammation value (PIIV) is an indicator assessing the overall inflammatory status within the body, but the relationship between PIIV and ROSC remains unclear.ObjectiveThis study aims to analyze the occurrence of ROSC and its influencing factors, and investigate the predictive value of PIIV, in order to provide insights for clinical prevention and treatment.MethodsClinical data of IHCA patients admitted to our hospital were retrospectively collected. Patients were divided into the ROSC group and non-ROSC group based on whether spontaneous circulation was restored after cardiopulmonary resuscitation. Multivariate logistic regression was used to analyze factors affecting ROSC, and the receiver operating characteristic (ROC) curve was employed to calculate the area under the curve (AUC) to evaluate the predictive value of PIIV.Results168 patients' clinical data were collected, including 62 patients with ROSC and 106 with non-ROSC. The results of multivariate logistic regression analysis showed that the duration of cardiopulmonary resuscitation, adrenaline dosage, blood lactate (Lac), and PIIV were independent influencing factors for ROSC in IHCA patients (P < 0.05). The ROC curve analysis revealed that the AUC of PIIV for predicting ROSC in IHCA patients was 0.805 (95% CI: 0.720–0.891), with an optimal cutoff value of 395.3, sensitivity of 83.33%, and specificity of 70.37%.ConclusionPIIV demonstrates valuable application in predicting ROSC in IHCA patients.